Sodium titanium phosphate and its uses
The use of a sodium titanium phosphate compound with a surface layer addresses the low cycle stability and high-rate discharge limitations of conventional water-based sodium secondary batteries, enhancing their performance through improved sodium ion diffusion and reduced polarization.
Patent Information
- Application Number
- JP2023505338
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-12
- Filing Date
- 2022-03-02
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2042-03-02
AI Technical Summary
Conventional water-based sodium secondary batteries face challenges with low cycle stability and limited high-rate charging and discharge characteristics, particularly when using Nati-type Na2(PO4)3 as a negative electrode active material.
A sodium titanium phosphate (NATP) compound with a specific surface layer composition and structure is used as a negative electrode active material, enhancing the battery's output characteristics by facilitating sodium ion diffusion and reducing polarization during charging and discharging.
The sodium titanium phosphate compound with a surface layer improves the cycle stability and high-rate discharge performance of sodium secondary batteries, offering superior output characteristics compared to conventional water-based batteries.
Smart Images

Figure 0007624186000002 
Figure 0007624186000003 
Figure 0007624186000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to sodium titanium phosphate and uses thereof. [Background technology]
[0002] Sodium secondary batteries, which do not use lithium, a rare metal, not only have advantages in terms of resources and cost, but also have the potential to be applied to new materials and have excellent high-rate charge and discharge characteristics. For sodium secondary batteries to date, those equipped with electrolytes similar to those used in current lithium secondary batteries, mainly non-aqueous electrolytes, have been considered. Recently, it has been reported that the narrow potential window of 1.23 V resulting from the decomposition of water, which was the greatest weak point of aqueous batteries, can be expanded to over 2 V by increasing the concentration of the electrolyte (Non-Patent Document 1), raising hopes for the practical application of aqueous sodium secondary batteries. In particular, for larger batteries, aqueous sodium secondary batteries using an aqueous electrolyte are suitable from the standpoints of cost and safety. Regarding the negative electrode material, which is another challenge for the practical application of aqueous sodium secondary batteries, Nasicon-type NaTi2(PO4)3 has been found to function, but it has low cycle stability and improvement of this is an issue (Non-Patent Document 2). [Prior art documents] [Non-patent literature]
[0003] [Non-Patent Document 1] Ruben-Simon et al, ACS Energy Letters,2,2005(2017) [Non-Patent Document 2] Sun Il Park et al, Journal of The Electrochemical Society,158(10)A1067-A1070(2011) Summary of the Invention [Problem to be solved by the invention]
[0004] The present disclosure has an object to provide at least one of sodium titanium phosphate, and further, a negative electrode active material that provides a sodium secondary battery having superior output characteristics compared to conventional aqueous sodium secondary batteries, and a sodium secondary battery equipped with the same, and in particular, an object to provide a negative electrode active material that provides an aqueous sodium secondary battery having higher output characteristics compared to conventional aqueous sodium secondary batteries equipped with Nasicon-type NaTi2(PO4)3 as the negative electrode active material. [Means for solving the problem]
[0005] In the present disclosure, it has been discovered that a sodium titanium phosphate composition having a surface layer containing a sodium titanium phosphate of a different composition has superior output characteristics compared to conventionally known negative electrode materials for sodium secondary batteries, and that by using this in the negative electrode, a sodium secondary battery with superior output characteristics can be constructed. That is, the present invention is as described in the claims, and the gist of the present disclosure is as follows.
[0006] [1] A surface layer containing Na5Ti(PO4)3, characterized by the general formula Na 1+x Sodium titanium phosphate, represented by Ti2(PO4)3 (where 0≦x≦2). [2] The sodium titanium phosphate according to the above [1], wherein the crystal structure of the sodium titanium phosphate is a Nasicon type crystal structure. [3] The surface layer is formed of the general formula Na 1+x The sodium titanium phosphate according to the above [1] or [2], which is more than 0 mass% and less than 5 mass% with respect to the sodium titanium phosphate represented by Ti2(PO4)3 (wherein 0≦x≦2). [4] The sodium titanium phosphate according to any one of [1] to [3] above, wherein the thickness of the surface layer is greater than 0 nm and less than or equal to 50 nm. [5] The sodium titanium phosphate according to any one of [1] to [4] above, having a crystallite size of 10 nm or more and 100 nm or less. [6] A method for producing sodium titanium phosphate according to any one of the above [1] to [5], comprising the steps of calcining a mixture containing a sodium source, a phosphate source, and a titanium source at 150°C or more and 400°C or less to obtain a primary calcined product, crushing the primary calcined product, and then calcining the product at 400°C or more and 900°C or less. [7] A negative electrode active material comprising the sodium titanium phosphate according to any one of [1] to [5] above. [8] A sodium secondary battery comprising a negative electrode containing the sodium titanium phosphate according to any one of [1] to [5] above, a positive electrode, and an electrolyte. [9] The sodium secondary battery according to the above [8], wherein the electrolyte is an aqueous electrolyte. Effect of the Invention
[0007] According to the present disclosure, it is possible to provide at least one of sodium titanium phosphate, a negative electrode active material that provides a sodium secondary battery with superior output characteristics compared to conventional aqueous sodium secondary batteries, and a sodium secondary battery equipped with the same. Furthermore, it is possible to provide a negative electrode active material that provides an aqueous sodium secondary battery with high output characteristics compared to conventional aqueous sodium secondary batteries equipped with Nasicon-type NaTi2(PO4)3 as the negative electrode active material. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 shows XRD patterns of the sodium transition metal phosphates of Examples 1 to 3 and a Comparative Example (a: Comparative Example 1, b: Example 1, c: Example 2, d: Example 3, e: PDF pattern (ICDD:33-1296 NaTi2(PO4)3). [Diagram 2] FIG. 2 shows XRD patterns of NaTi2(PO4)3 in Examples 5 and 6 (f: Example 5, g: Example 6, h: PDF pattern (Na5Ti(PO4)3). [Figure 3A] FIG. 3A is a cross-sectional TEM image of the sodium transition metal phosphate of Example 2. [Figure 3B]FIG. 3B is a cross-sectional TEM image of the sodium transition metal phosphate of Comparative Example 1. [Figure 4] FIG. 4 shows the results of the charge-discharge cycle test of Examples 1 to 3 and Comparative Example 1 (a(▲): Example 1, b(■): Example 2, c(◆): Example 3, d(●): Comparative Example 1). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, the sodium titanium phosphate of the present disclosure will be described with reference to an example of an embodiment.
[0010] <Sodium titanium phosphate> The present embodiment is a ferroelectric material having the general formula NaTi(PO)3 and a surface layer containing NaTi(PO). 1+x It is a sodium titanium phosphate represented by Ti2(PO4)3 (where 0≦x≦2). By having a surface layer containing Na5Ti(PO4)3, the sodium ions (Na + ) becomes easier to spread. The NaTP salt in this embodiment is a phosphoric acid compound containing sodium and titanium, and specifically has the general formula Na 1+x Ti2(PO4)3 (where 0≦x≦2) is a sodium titanium phosphate, and is NaTi2(PO4)3 (i.e., the general formula Na 1+x It is more preferable that x=0 in Ti2(PO4). In this embodiment, the composition of the NaTP salt can be determined by a known composition analysis method, such as inductively coupled plasma optical emission spectrometry (ICP analysis), atomic absorption spectrometry, TEM-EDS, etc., and can be determined by ICP analysis using a general ICP optical emission spectrometer (ICPS-8100, manufactured by Shimadzu Corporation). The NaTP salt of this embodiment preferably has a Nasicon type crystal structure (so-called Nasicon type NaTP salt). The Nasicon type crystal structure can be identified by comparing the XRD pattern of the NaTP salt of this embodiment with the PDF pattern (ICDD:33-1296 NaTi2(PO4)3).
[0011] The NaTP salt of this embodiment has a surface layer containing Na5Ti(PO4)3 (hereinafter, simply referred to as the "surface layer"). 1+x Compared to sodium titanium phosphate represented by Ti2(PO4)3 (where 0≦x≦2), the surface layer has a composition that is excess sodium, and it is believed that this surface layer functions as a sodium buffer layer during high-power discharge, resulting in high power characteristics. The surface layer may be present on at least a part of the NaTP salt without inhibiting the diffusion of sodium, and is preferably present on at least a part of the surface of the NaTP salt. The form in which the surface layer is present on at least a part of the NaTP salt includes at least the presence of NaTP salt and Na5Ti(PO4)3 via the interface between the two, that is, the surface layer forms an interface with the NaTP salt. As a result of the interface between NaTP salt and Na5Ti(PO4)3, it is considered that the diffusion coefficient of sodium is equivalent to that of NaTP salt without a surface layer. The surface layer does not need to cover the entire surface of the NaTP salt, and may be in the form of islands in the sea. That is, the surface layer may be at least one of Na5Ti(PO4)3 and a composition containing Na5Ti(PO4)3, preferably Na5Ti(PO4)3, present on at least a part of the surface of the NaTP salt. The surface layer only needs to contain Na5Ti(PO4)3, and may contain TiO2 in addition to Na5Ti(PO4)3, but is preferably made of Na5Ti(PO4)3, and more preferably made of Na5Ti(PO4)3 whose crystal structure is a Nasicon type structure. The NaTP salt of the present embodiment may have a surface layer on the entire surface or at least a part of the surface, and may have a surface layer on at least a part of the surface. The NaTP salt particle may have Na5Ti(PO4)3 on the entire surface or at least a part of the surface, preferably at least a part of the surface. The nature of Na5Ti(PO4)3 contained in the surface layer is not particularly limited, and may be at least one of crystalline and amorphous, and may be at least one of dense and porous. Furthermore, the surface layer preferably contains Na5Ti(PO4)3 produced by the reaction of the sodium source, phosphorus source, and titanium source on the surface of the NaTP salt. This makes it easier to suppress polarization (hysteresis) during charge and discharge cycles. The presence of the surface layer, which is a coating film, can be confirmed by TEM observation (transmission electron microscope observation). In TEM observation, the surface layer is observed as a visual field image different from that of the NaTP salt, and the surface layer is observed as a visual field image with a darker tone than that of the NaTP salt.
[0012] Sodium ion (Na + ) tends to be easily diffused, so the ratio of the surface layer in this embodiment (hereinafter also referred to as "coating amount") is preferably such that the lower limit exceeds 0% by mass, more preferably 0.01% by mass or more, and even more preferably 0.1% by mass or more, relative to the NaTP salt. The upper limit is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 5% by mass or less, relative to the NaTP salt. Any combination of the upper limit and lower limit may be used. Therefore, the ratio of the surface layer in this embodiment is preferably, for example, such that the ratio exceeds 0% by mass and 20% by mass or less, more preferably 0.01% by mass or more and 15% by mass or less, and even more preferably 0.1% by mass or more and 5% by mass or less, relative to the NaTP salt. Any method for measuring the coating amount may be used, and for example, quantitative analysis using TEM-EDS may be used. If the coating amount exceeds 20% by mass, a surface layer that does not inhibit the diffusion of sodium is not formed, and the diffusion coefficient of sodium ions is significantly reduced. The thickness of the surface layer is arbitrary, provided that it is thick enough not to impede the diffusion of sodium. The thickness of the surface layer is preferably such that the lower limit exceeds 0 nm, and is more preferably 0.1 nm or more. The upper limit is preferably 50 nm or less, more preferably 40 nm or less, and even more preferably 5 nm or less. Any combination of these upper and lower limits is acceptable. Therefore, the thickness of the surface layer in this embodiment is preferably, for example, more than 0 nm and 50 nm or less, and even more preferably 0.1 nm or more and 5 nm or less. The thickness of the surface layer can be determined by TEM observation, and the thickness of the surface layer observed in the TEM observation diagram (i.e., the surface layer can be confirmed in the TEM observation diagram, and the maximum thickness of the surface layer observed in the TEM observation diagram) is more than 0 nm or 0.1 nm or more, and is 50 nm or less, 40 nm or less, 5 nm or less, or 3 nm or less. The crystallite size of the NaTP salt of this embodiment is preferably 10 nm or more, more preferably 20 nm or more, and even more preferably 30 nm or more. The upper limit is preferably 100 nm or less, more preferably 50 nm or less, and even more preferably 40 nm or less. Any combination of these upper and lower limits is acceptable. Therefore, the crystallite size of the NaTP salt of this embodiment is preferably, for example, 10 nm or more, 100 nm or less, or 20 nm or more, 50 nm or less, or even 20 nm or more, 40 nm or less, or even 30 nm or more, 40 nm or less. By having the crystallite size in this range, the NaTP salt of this embodiment is more likely to efficiently intercalate and deintercalate sodium, and is expected to have high output characteristics as a negative electrode active material for a sodium secondary battery. In this embodiment, the "crystallite size" refers to the crystallite having the general formula Na 1+x The diameter (hereinafter also referred to as the "WH diameter") is determined by the Williamson-Hall method from two or more XRD peaks belonging to the XRD pattern of sodium titanium phosphate represented by Ti2(PO4)3 (where 0≦x≦2). Specifically, the general formula Na 1+x Two or more XRD peaks that can be assigned to Ti2(PO4)3 (where 0≦x≦2), preferably the general formula Na 1+xFor all XRD peaks attributable to Ti2(PO4)3 (where 0≦x≦2), the following plot is made. The following linear approximation is determined by the least squares method for the resulting plots of multiple points, and the reciprocal of the y-intercept of the linear approximation is the crystallite size. <Plot> Y=(β sinθ) / λ X=sinθ / λ <First-order approximation formula> Y = 2η·X + (1 / ε) (1 equation) In these formulas, β is the half-width (°), θ is the diffraction angle (°), λ is the wavelength of the radiation source (nm), η is the non-uniform distortion, and ε is the crystallite diameter (Å), and 1 / ε in the linear approximation formula is the y-intercept. In addition, in the calculation of the WH diameter in this embodiment, there is no particular limitation on the XRD peak to be used, and for example, all XRD peaks that belong to NaTP may be used. The NaTP salt of this embodiment exhibits high output characteristics when used as a negative electrode active material in a sodium secondary battery. The configuration of the sodium secondary battery and the conditions of the charge / discharge test are described below. (Sodium secondary battery) Electrolyte: 17mol / kg NaClO4 aqueous solution Negative electrode: 70% by mass of NaTP salt, 25% by mass of acetylene black, and Anode made of 5% polytetrafluoroethylene Positive electrode: 70% by mass of Na2Ni[Fe(CN)6], 25% by mass of acetylene black, and Positive electrode made of 5% polytetrafluoroethylene (Charge / discharge test conditions) Current density: (1 to 5 cycles) 2mA / cm 2 (6-10 cycles) 5mA / cm 2 (11-15 cycles) 10mA / cm 2 (16-20 cycles) 15mA / cm 2 (21-25 cycles) 20mA / cm 2 (25-30 cycles) 25mA / cm 2 (31-35 cycles) 2mA / cm 2 Voltage: -0.9V~-0.3V (vs Ag / AgCl reference electrode) Charge / discharge temperature: 25℃
[0013] <Method of producing NaTP salt having a surface layer> The method for producing the NaTP salt of this embodiment is arbitrary, but may include a production method having a step of calcining a mixture containing a sodium source, a phosphate source, and a titanium source at 150° C. to 400° C. to obtain a primary calcined product, which is then crushed and calcined at 400° C. to 900° C. (hereinafter also referred to as the “calcination step”). This makes it possible to obtain a NaTP salt having a surface layer containing Na5Ti(PO4)3. The mixture subjected to the firing step contains a sodium source, a phosphate source, and a titanium source (hereinafter, these are also collectively referred to as "precursors"), and is a composition containing the precursors. The sodium source may be any compound containing sodium (Na), and is preferably one or more selected from the group consisting of sodium carbonate, sodium hydroxide, and sodium chloride, more preferably at least one of sodium carbonate and sodium hydroxide, and even more preferably sodium carbonate. The phosphate source may be any compound containing phosphoric acid (PO4), and is preferably one or more selected from the group consisting of pyrophosphoric acid, polyphosphoric acid, and ammonium dihydrogen phosphate, and more preferably ammonium dihydrogen phosphate. The titanium source may be any compound containing titanium (Ti), and may be at least one of titanium oxide and organic titanium compound. A preferred titanium oxide is titania (TiO2), and a preferred organic titanium compound is one or more selected from the group consisting of titanium-containing alkoxide, acylate and chelate compounds, titanium-containing alkoxide, or titanium tetrabutoxide (Ti(OCH2CH2CH2CH3)4). A preferred titanium source is titanium tetrabutoxide. Particularly preferred precursors include sodium carbonate, diammonium hydrogen phosphate and titanium tetrabutoxide. The composition of the mixture is in particular of the general formula Na 1+x It is preferable that the composition is such that sodium is in excess relative to sodium titanium phosphate represented by Ti2(PO4)3 (where 0≦x≦2). For example, the ratio of Na [mol] to Ti [mol] in the mixed composition is more than 1.0 or 1.1 or more, and is 3 or less, 2 or less, or 1.5 or less. It is believed that by having such a composition, a surface layer is formed on the surface of the NaTP salt particles through the preliminary firing and main firing described below. Such a mixture can be used to obtain the desired Na 1+x The precursor may be mixed with sodium titanium phosphate represented by Ti2(PO4)3 (where 0≦x≦2) to obtain a composition with excess sodium. For example, when producing NaTP salt represented by NaTi2(PO4)3, the sodium source and titanium source may be mixed in such a way that the ratio of Na[mol] to Ti[mol] is greater than 0.5 or greater than 0.55, and is 1.5 or less, 1 or less, or 0.75 or less. When producing NaTP salt represented by Na2Ti2(PO4)3, the sodium source and titanium source may be mixed in such a way that the ratio of Na[mol] to Ti[mol] is greater than 1.0 or greater than 1.1, and is 3 or less, 2 or less, or 1.5 or less. The mixture is obtained by mixing the precursors uniformly. The mixing method can be at least one of wet mixing and dry mixing, and further wet mixing can be exemplified. A particularly preferred mixing method can be a method of drying a mixed solution containing the precursors and a solvent after stirring or while stirring. The solvent can be at least one of water and alcohol, and further water. The stirring can be performed under conditions that allow the precursors to be mixed uniformly, and can be exemplified by stirring the mixed solution at a stirring speed of 100 to 500 rpm, and the stirring speed can be increased as the amount of the mixed solution increases. The drying can be performed under conditions that allow the solvent to be removed from the mixed solution, and can be exemplified by air at 60°C or higher or 70°C or higher, and 150°C or lower, 120°C or lower, or 100°C or lower. This can obtain a mixture in which the precursors are mixed in a uniform state. In the manufacturing method of this embodiment, the mixture is fired at 150°C or more and 400°C or less. As a method of firing to obtain a primary fired product (hereinafter also referred to as "pre-firing"), firing in an oxidizing atmosphere, preferably in air, at 150°C or more, 250°C or more, or 300°C or more and 400°C or less, less than 400°C, or 370°C or less can be mentioned. The time of pre-firing is optional, but can be 30 minutes or more and 10 hours or less. It is considered that the sodium concentration becomes gradient composition between the surface and the inside of the particles of the mixture, and the sodium concentration is higher on the particle surface than in the particle inside by pre-firing. After the preliminary firing, the resulting primary fired product is crushed by any method that can remove loose agglomerates of the primary fired product, such as dry grinding using a mortar. In the production method of this embodiment, the primary fired product after crushing is fired at 400°C or more and 900°C or less (hereinafter also referred to as "main firing"). Examples of the main firing method include firing in an oxidizing atmosphere, preferably in the air, at a temperature of 400°C or more, more than 400°C or more, or 600°C or more, and 900°C or less, 800°C or less, or 750°C or less. The time for main firing is arbitrary, but examples include 30 minutes to 10 hours. By main firing, NaTP salt having a surface layer is produced from a mixture having a composition with a gradient sodium concentration.
[0014] <Negative electrode active material> Next, a negative electrode active material containing the NaTP salt of the present disclosure will be described with reference to an example of an embodiment. In this embodiment, the "negative electrode active material" refers to an electrode active material of an electrode having a lower potential among the electrodes constituting an electrochemical device, and in particular, an electrode active material of the negative electrode of a sodium secondary battery. The negative electrode active material of this embodiment may contain the NaTP salt of this embodiment (i.e., the NaTP salt having a surface layer) or may consist of only the NaTP salt of this embodiment (i.e., only the NaTP salt having a surface layer). On the other hand, the negative electrode active material of this embodiment may contain an active material other than the NaTP salt of this embodiment, such as an active material such as a sodium transition metal compound. The negative electrode active material of this embodiment may have a coating layer, preferably a coating layer having electrical conductivity (i.e., a conductive layer), on a part or the whole of the surface of the negative electrode active material, such as a carbon layer. In this case, the coating layer may be on the surface layer containing Na5Ti(PO4)3. However, the coating layer may be on the surface of the NaTP salt.
[0015] <Sodium secondary battery> Next, a sodium secondary battery characterized by including a negative electrode containing the NaTP salt of the present disclosure, a positive electrode, and an electrolyte solution will be described with reference to an example of an embodiment. In this embodiment, the term "sodium secondary battery" refers to a battery that uses sodium ions (Na + A sodium secondary battery is an electrochemical device in which charging and discharging occurs through the insertion and removal of ions, and is synonymous with sodium secondary battery, sodium ion secondary battery, sodium ion battery, sodium storage battery, Na secondary battery, Na ion battery, or Na storage battery. A "nonaqueous electrolyte" is an electrolyte that contains a nonaqueous solvent as a solvent, and an "aqueous electrolyte" is an electrolyte that contains an aqueous solvent as a solvent. A "nonaqueous sodium secondary battery" is a sodium secondary battery that has a nonaqueous electrolyte as the electrolyte, and an "aqueous sodium secondary battery" is a sodium secondary battery that has an aqueous electrolyte as the electrolyte.
[0016] <Negative electrode> The negative electrode may include a negative electrode mixture containing a negative electrode active material containing the NaTP salt of this embodiment, and a current collector. The negative electrode mixture contains a negative electrode active material, a binder, a conductive material, and, if necessary, an additive. The binder, the conductive material, and the additive may each be a known material. The binder may be one or more selected from the group consisting of fluororesin, polyethylene, polypropylene, SBR material, and imide material, and may further be one or more selected from the group consisting of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and ethylenetetrafluoroethylene (ETFE). The conductive material may be one or more selected from the group consisting of carbon materials, conductive fibers such as metal fibers, metal powders such as copper, silver, nickel, and aluminum, and organic conductive materials such as polyphenylene derivatives. Preferred carbon materials include graphite, soft carbon, hard carbon, carbon black, ketjen black, acetylene black, activated carbon, carbon nanotubes, carbon fibers, and mesoporous carbon. The negative electrode mixture may be produced by a known method, and may be produced by mixing a negative electrode active material, a binder, and a conductive material in a desired ratio.
[0017] <Positive electrode> The positive electrode may include a positive electrode mixture containing a positive electrode active material, a current collector, and, if necessary, an additive. The positive electrode mixture contains a positive electrode active material, a binder, a conductive material, and, if necessary, an additive. The positive electrode active material may contain a material that does not prevent the insertion and desorption of sodium ions from the negative electrode active material, and examples of the material include at least one of a sodium-containing transition metal oxide, a sodium-containing polyanion compound, and a carbon-based material. The binder and conductive material may be any known material, and may be the same as the binder and conductive material that can be used in the negative electrode mixture described above. The positive electrode mixture may be produced by a known method, and may be produced by mixing a positive electrode active material, a binder, and a conductive material in a desired ratio.
[0018] <Electrolyte> The electrolytic solution is either a non-aqueous electrolytic solution or an aqueous electrolytic solution, and is preferably an aqueous electrolytic solution. The electrolyte is a sodium salt, and a soluble sodium salt is preferable. Preferred electrolytes include one or more selected from the group consisting of NaCl, Na2SO4, NaNO3, NaClO4, NaOH, and Na2S. From the viewpoint of ease of handling, the electrolyte is preferably one or more selected from the group consisting of NaCl, Na2SO4, NaNO3, and NaClO4, and more preferably at least one of NaCl and NaClO4. The electrolyte concentration in the electrolytic solution is not particularly limited, but from the viewpoint of increasing the energy density of the sodium secondary battery, it is preferable that the electrolyte concentration (sodium salt concentration) in the electrolytic solution is high, and an example of the sodium salt concentration is a concentration of 1 mol / kg (1 m) or more and equal to or less than the saturated solubility. The electrolyte may contain an additive. The additive is not particularly limited, but may be one or more selected from the group consisting of succinic acid, glutamic acid, maleic acid, citraconic acid, gluconic acid, itaconic acid, diglycol, cyclohexanedicarboxylic acid, cyclopentanetetracarboxylic acid, 1,3-propanesultone, 1,4-butanesultone, methyl methanesulfonate, sulfolane, dimethylsulfone, and N,N-dimethylmethanesulfonamide. The content of the additive may be, for example, 0.01% by mass or more and 10% by mass or less as a mass ratio of the additive to the mass of the electrolyte.
[0019] <Other configurations> Other components such as the current collectors of the positive and negative electrodes and the separator may be any known components used in sodium secondary batteries or lithium secondary batteries. A sodium secondary battery having a negative electrode containing the NaTP salt of this embodiment exhibits high cycle stability compared to conventional sodium secondary batteries, particularly conventional aqueous sodium secondary batteries having Nasicon-type NaTi2(PO4)3 as the negative electrode active material. EXAMPLES
[0020] Next, the present disclosure will be described with reference to examples. However, the present disclosure is not to be construed as being limited to these examples.
[0021] <Evaluation of crystallinity> The crystal structure of the NaTP salt was identified using a desktop X-ray analyzer (instrument name: MiniFlex600 / ASC-8, manufactured by Rigaku Corporation) under the following conditions. Target: Cu Output: 0.6kW (15mA-40kV) Step scan: 0.02°(2θ / θ) Measurement time: 0.05 seconds
[0022] <Composition analysis> The composition of NaTP salt was determined by dissolving 50 mg of sample in an aqueous solution containing 10 mL of 35% hydrochloric acid and 1 mL of 35% hydrogen peroxide, and then performing ICP analysis on the solution. The ICP analysis was performed using an ICP emission spectrometer (instrument name: ICPS-8100, manufactured by Shimadzu Corporation).
[0023] <Observation of the surface layer> The observations were performed using a transmission electron microscope (instrument name: JEM-2100, manufactured by JEOL Ltd.) and a thermal field emission scanning electron microscope (instrument name: JSM-7600F, manufactured by JEOL Ltd.).
[0024] <Sodium secondary battery> (Preparation of positive electrode) Nickel hexacyanoferrate Na2Ni([Fe(CN)6] with a cubic crystal structure was used as the positive electrode active material. Na2Ni([Fe(CN)6] was synthesized in the following manner: 2.69 g of 10 mmol of Ni(OCOCH3)2·4H2O was dissolved in 175 mL of H2O and 25 mL of DMF (N,N-dimethylformamide, HCON(CH3)2) to obtain the first solution; on the other hand, 4.84 g of 10 mmol of Na4[Fe(CN)6]·10H2O and 7 g of NaCl were dissolved in 175 mL of H2O to obtain the second solution. The first solution was slowly added to the second solution, and the mixture was stirred at room temperature for 72 hours to give a precipitate, which was collected by centrifugation, washed with methanol, and then dried in air to give nickel hexacyanoferrate (Na2Ni[Fe(CN)6]) with a cubic crystal structure. The obtained Na2Ni([Fe(CN)6], acetylene black (hereinafter also referred to as "AB"), and polytetrafluoroethylene (hereinafter also referred to as "PTFE") were mixed in a mass ratio of 70:25:5, and then molded into pellets with a diameter of 3 mm to form a positive electrode (positive electrode mixture).
[0025] (Preparation of negative electrode) The negative electrode active material and AB were mixed in a planetary ball mill at 400 rpm for 1 hour under an Ar atmosphere so that the mass ratio was 84:16. The mixture was then subjected to carbothermal treatment in an Ar stream at 800°C for 1 hour, after which PTFE was mixed in a mass ratio of 95:5 and formed into pellets with a diameter of 2 mm to form the negative electrode (negative electrode mixture).
[0026] (Preparation of aqueous sodium secondary battery) An aqueous sodium secondary battery was fabricated with a positive electrode mixture as the working electrode (electrode corresponding to the positive electrode), a negative electrode mixture as the counter electrode (electrode corresponding to the negative electrode), a silver chloride electrode (Ag / AgCl) as the reference electrode, and an aqueous NaClO4 solution with an electrolyte concentration (NaClO4 concentration) of 17 mM as the electrolyte.
[0027] (Synthesis of NaTP salt) <Example 1> A mixed solution was obtained by mixing 2 times the molar amount of citric acid and 2 times the molar amount of hydrogen peroxide (H2O2) with respect to Ti(OCH2CH2CH2CH3)4 in 40mL of ethanol solution in which Ti(OCH2CH2CH2CH3)4 was dissolved. After adding 1.05 times the molar amount of Na2CO3 (0.525 as the molar ratio of Na to Ti) and 1 times the molar amount of NH4H2PO4 with respect to Ti(OCH2CH2CH2CH3)4 in the obtained mixed solution, this was stirred at 500 rpm and evaporated to dryness at 60°C for 30 minutes, and then at 80°C for 1 to 2 hours. After that, the solid obtained by heating at 350°C for 5 hours in the air was crushed and mixed, and heated at 700°C for 12 hours in the air to obtain NaTi2(PO4)3 having a surface layer containing Na5Ti(PO4)2, which was used as the NaTP salt of this example. The crystallite size of the NaTP salt in this example was 36 nm, and the mass proportion of the surface layer was 1 mass %. Using a planetary ball mill, the obtained NaTP salt and AB were mixed for 1 hour at 400 rpm under an argon atmosphere so that the mass ratio was 84:16. The obtained mixture was fired at 800°C for 1 hour in an argon stream to obtain a negative electrode active material containing NaTi2(PO4)3 of a Nasicon type structure having a surface layer (Nasicon type NaTi2(PO4)3).
[0028] <Example 2> The NaTi2(PO4)3 with a surface layer and the negative electrode active material were obtained by the same method as in Example 1, except that Na2CO3 was used in an amount of 1.1 times by mole (the molar ratio of Na to Ti was 0.55). The crystallite size of the NaTP salt in this example was 38 nm, and the mass ratio of the surface layer was 2 mass%.
[0029] <Example 3> Except for the fact that Na2CO3 was used in a molar amount of 1.15 times (the molar ratio of Na to Ti was 0.575), NaTi2(PO4)3 with a surface layer and a negative electrode active material were obtained in the same manner as in Example 1. The crystallite size of the NaTP salt in this example was 41 nm.
[0030] <Example 4> Except for the fact that Na2CO3 was used in a molar amount of 1.2 times (the molar ratio of Na to Ti was 0.6), NaTi2(PO4)3 with a surface layer and a negative electrode active material were obtained in the same manner as in Example 1. The crystallite diameter of the NaTP salt in this example was 49 nm.
[0031] <Example 5> Except for the fact that Na2CO3 was used in a molar amount of 1.5 times (the molar ratio of Na to Ti was 0.75), NaTi2(PO4)3 with a surface layer and a negative electrode active material were obtained in the same manner as in Example 1. The crystallite size of the NaTP salt in this example was 50 nm.
[0032] <Example 6> Except for using twice the molar amount of Na2CO3 (the molar ratio of Na to Ti is 1), the NaTi2(PO4)3 with a surface layer and the negative electrode active material were obtained in the same manner as in Example 1. The crystallite size of the NaTP salt in this example was 50 nm.
[0033] <Comparative Example 1> Except for using 1x Na2CO3 (0.5 molar ratio of Na to Ti), the same method as in Example 1 was used to obtain NaTi2(PO4)3 and a negative electrode active material with a Nasicon structure that does not have a surface layer containing Na5Ti(PO4)3. The crystallite size of the NaTP salt in this comparative example was 34 nm.
[0034] The XRD patterns of the negative electrode active materials obtained in the examples and comparative examples are shown in Figures 1 and 2. In all cases, the XRD peak of NaTi2(PO4)3 was confirmed. In Examples 5 and 6, the XRD peaks attributed to Na5Ti(PO4)3 were also confirmed, and it was found that in the examples, NaMP salt having a surface layer (coating layer) containing Na5Ti(PO4)3 was obtained. FIG. 3A shows a cross-sectional TEM observation diagram of NaTi2(PO4)3 of Example 2. FIG. 3B shows a cross-sectional TEM observation diagram of NaTi2(PO4)3 of Comparative Example 1. In NaTi2(PO4)3 of Example 2, NaTi2(PO4)3 is white, the surface layer containing Na5Ti(PO4)3 is gray, and the outside of the particle (background) is black (see FIG. 3A). From this, it was confirmed that there is a surface layer of 2 to 7 nm, or even 5 nm, between NaTi2(PO4)3 and the particle. In contrast, in NaTi2(PO4)3 of Comparative Example 1, NaTi2(PO4)3 is gray, and the outside of the particle (background) is black (see FIG. 3B). From FIG. 3A and FIG. 3B, it was confirmed that the surface structure of the particles of NaTi2(PO4)3 is different between Example 2 and Comparative Example 1, and that the surface layer exists on the surface of the particle of NaTi2(PO4)3 of Example 2.
[0035] <Measurement Example 1> (Charge-discharge cycle test) Using an aqueous sodium secondary battery equipped with the negative electrode active material of the Example or Comparative Example, charging and discharging were repeated under the following conditions, and the discharge capacity of each charge / discharge cycle was measured. The ratio (%) of the discharge capacity at the 30th cycle to the discharge capacity at the 1st cycle was taken as the capacity retention rate, and the output characteristics were evaluated based on this. Current density: (1 to 5 cycles) 2mA / cm 2 (6-10 cycles) 5mA / cm 2 (11-15 cycles) 10mA / cm 2 (16-20 cycles) 15mA / cm 2 (21-25 cycles) 20mA / cm 2 (26-30 cycles) 25mA / cm 2 (31-35 cycles) 2mA / cm 2 Voltage: -0.9V~-0.3V (vs Ag / AgCl reference electrode) Charge / discharge temperature: 25℃ The discharge capacities for cycles 1 to 35 are shown in Figure 4. The capacity retention rates are shown in Table 1 below.
[0036] [Table 1] From Figure 4, 20mA / cm 2 In high-output discharges exceeding 1000 mA, the charge / discharge capacity of the NaTP salt having a surface layer (coating layer) was large, and this tendency was more pronounced in Examples with a smaller amount of Na2CO3, which is thought to affect the composition of the surface layer. After 30 cycles, the discharge current density was 2mA / cm 2 As a result of charging and discharging at this temperature, the discharge capacities of the examples and the comparative examples were similar. This confirmed that the surface layer had little effect on the cycle characteristics and suppressed the capacity decrease during high-output discharge, i.e., charging and discharging at a high current density.
[0037] This application claims priority to Japanese patent application No. 2021-39890, filed on March 12, 2021, and incorporates all of the contents of that Japanese patent application by reference.
Claims
1. Na 5 Ti(PO 4 ) 3 having a surface layer containing the general formula Na 1+x Ti 2 (P.O. 4 ) 3 (where 0≦x≦2), Sodium titanium phosphate, wherein the surface layer is more than 0 mass % and less than 5 mass % of sodium titanium phosphate represented by the general formula Na1+xTi2(PO4)3 (where 0≦x≦2).
2. 2. The sodium titanium phosphate according to claim 1, wherein the crystal structure of said sodium titanium phosphate is a Nasicon type crystal structure.
3. 3. The sodium titanium phosphate according to claim 1 or 2, wherein the surface layer is made of Na 5 Ti(PO 4 ) 3 having a Nasicon type crystal structure.
4. The sodium titanium phosphate according to any one of claims 1 to 3, wherein the thickness of the surface layer is greater than 0 nm and not greater than 50 nm.
5. 5. The sodium titanium phosphate according to claim 1, having a crystallite size of 10 nm or more and 100 nm or less.
6. 6. A method for producing sodium titanium phosphate according to claim 1, comprising the steps of calcining a mixture containing a sodium source, a phosphate source and a titanium source at 150° C. or more and 400° C. or less to obtain a primary calcined product, crushing the primary calcined product, and then calcining the product at 400° C. or more and 900° C. or less.
7. A negative electrode active material comprising the sodium titanium phosphate according to claim 1 .
8. A sodium secondary battery comprising a negative electrode containing the sodium titanium phosphate according to any one of claims 1 to 5, a positive electrode, and an electrolyte.
9. 9. The sodium secondary battery according to claim 8, wherein the electrolyte is an aqueous electrolyte.
Citation Information
Patent Citations
Mixed electrolyte aqueous rechargeable nickel sodium / lithium battery and preparation method thereof
CN108091921A
Glass ceramics and method for producing the same
JP2011241138A
Aqueous solution system secondary battery
JP2012054208A
Positive electrode active material composite for lithium ion secondary battery or positive electrode active material composite for sodium ion secondary battery, secondary battery including the same, and method of manufacturing the same
JP2019175830A
Negative electrode active material for electricity storage devices
WO2017026228A1